Global Trends Research on Urgency of Inclusive Education and It’s Thematic Mapping: A Systematic Literature Review - Muhammad Fikri Fauzi Faize; Nadia Amalia (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Inclusive education is a form of education that upholds the values of equality and equal rights, ensuring that every child receives an education, regardless of physical or cognitive limitations. This study aims to analyze global trends in 'inclusive education' using the PRISMA method from 2017 to 2026, drawing on the Dimensions AI database. The data was accessed on February 7, 2026, by entering the keyword "Inclusive Education." A total of 2,156,768 works appeared at the start of the search, leaving only 40,924 articles that met the research criteria. The research results show that the global research trend on "Inclusive Education" continues to grow year over year, from 1,002 publications in 2017 to 15,286 in 2025, with 1,064 publications in 2026. These results indicate that related research has received strong attention from the education community. The discussion of the research results is also enriched with visualizations from VOSviewer, including several types of visualizations. A total of 209 items in 6 clusters are recorded in the VOS Viewer visualization, with a minimum of 10 mentions. Umesh Sharma from Monash University, Australia, is the most active researcher, while the International Journal of Inclusive Education is the most active in related research. The results of this mapping serve as a guideline for further, more targeted, and impactful research on inclusive education.